A New Philosophy of Communication: Agenda-Setting 2.0 - Gherab Martin, Karim (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
The philosophy of communication of the 20th century accepted, in general terms, the agenda-setting theory proposed by McCombs and Shaw (1972). This theory underlined the capacity of the mass media to shape the understanding that the general public has of social reality (Wolf, 1987). However, the Internet and social networks have radically changed the landscape, since the traditional mainstream media are now in tow of what is trending-topic on the social media. This article points out the need to develop a new philosophy of communication, adapted to the existence of a new technological and social framework, which will redefine the patterns and factors that currently shape the public agenda (agenda-setting 2.0).